PENGARUH KEPERCAYAAN, KUALITAS LAYANAN DAN PERSEPSI HARGA TERHADAP KEPUASAN PENUMPANG KERETA API EKONOMI KALIGUNG JURUSAN WELERIâTEGAL (Studi Pada Penumpang di Stasiun Weleri) - Nur Hafifi Safitri, 13.05.51.0013; Basiya, R. (Students Journal of Economic and Management, 2017)
The study examines the effect trust, services quality, and price perception of the passenger satisfaction a Kaligung trains of economic Weleri-Tegal. This research was conducted at the Weleri rail station by using a go public transportation service company as the unit analysis.The sampling method used purposive sampling with the observation period from 2016-2017. Relationships and (or )influence between variable described by using multiple regression analysis.The result showed that trust has positive effect and significant to the passenger satisfaction a Kaligung trains of economic Weleri-Tegal. The result showed that service quality has positive effect and significant to the passenger satisfaction a Kaligung trains of economic Weleri-Tegal.The result showed that priceperception has positive effect and significant to the passenger satisfaction a Kaligung trains of economic Weleri Tegal. Keyword : Trust, Service Qualiy, Price Perception, Satisfaction a passenger Train.